Kebijakan Pemerintah Dalam Mengatasi Eksternalitas Dan Pengelolaan Sampah Plastik Di Kota Jayapura - Tanan, Christina Irwati; Duri, Jimmi Ari (2021)
This study aims to determine the externalities of plastic waste and government policies on the problem and processing of plastic waste in Jayapura City in 2017-2019. This data research was conducted at the Jayapura City Environment and Cleanliness Service Office, namely data on regulations, instructions for 2017-2019. This research method uses qualitative data analysis techniques with data collection techniques through interview techniques, observation, and documentation methods, and literature study. The results showed that the externality of plastic waste in Jayapura City increased due to the use of plastic or plastic packaging materials, consumption of bottled drinks, lack of awareness of the community to dispose of garbage in its place, and the increasing population in Jayapura City. The Jayapura City Government's policies in overcoming the problem and processing of plastic waste are the basis of a Circular of the Minister of the Environment, a Circular on Reducing Plastic Waste through the Application of Non-Free Single-Use Plastic Shopping Bags, Circular on Reducing the Use of Plastic Bags, Socialization, Jayapura City Mayor Regulation regarding Policy and the Jayapura City Regional Strategy in the management of household waste and household-like waste, and the Jayapura Mayor's Instruction on the Application of Using alternative shopping bags to replace plastic bags in Jayapura city. Besides, the waste bank program, the plastic waste recycling program, the climate village program. So that the impact of decreasing the use of plastic bags in the modern market has resulted in a decrease in plastic waste, although not yet fully effective because the Government Policy has not been applied to traditional markets. This research is expected to be an input for the Jayapura City Government in making policies regarding the problem of plastic waste and its management. So that it can reduce the amount of plastic waste and its impact on society and the environment.